Lebanese Investors’ Decision Making Analysis from Conventional and Behavioral Perspectives Simultaneously - Ghalayini, Latifa; Alkees, Sally Ziad (Journal of Economics and Behavioral Studies, 2021)
The investment decision Process varies from one individual to another and from one country to another respectively. These decisions are usually taken based on either a Conventional basis or linked to the sentimental side of investors and reflected through behavioral finance gateway, where biases and psychological side of investors control their way of thinking and affect their investment decisions endlessly. Furthermore, based on previous literature the majority of investors tend to incorporate both gateways during their investment process as they don’t depend solely on Conventional gate, but their psychological part appears to play a big role while deciding and similarly for Lebanon. However, the main aim of this paper lies in investigating the main factors from both gates triggering Lebanese individual investors’ decision-making during their investment process. Moreover, the empirical part lies on focusing on a bunch of samples from individual Lebanese investors distributed along with most Lebanese districts; where 211 complete responses are interpreted within the SPSS program, undergoing factor analyses and Regression models. Results obtained indicates that Lebanese individual investors tend to incorporate both gateways in their investments decision, where the main goal stays utility and profit maximization; that to say tending to seek profits regardless of the investment field and approach. Nevertheless, during seeking profits Lebanese investor is being exposed to certain behavioral errors and biases that appear to impact and control his decisions significantly during investment making the process so far, and theses biases are affecting the Lebanese individual investors clearly more than that of conventional ones.